Oil Composition of Pilis: An Indonesian Forehead Topical Herbal Medicine - Timotius, Kris Herawan; Santoso, Adit Widodo; Sari, Ita Novita (Pharmacognosy Communications)
Pilis is a type of jamu (Indonesian herbal medicine) applied to the forehead to cure dizziness, hazy vision and eyestrain. At the moment, pilis can be obtained from large jamu factories, local jamu producers, and home-based producers. Information on the diversity of pilis quality from producers is needed to determine the most essential bioactive compounds in Pilis. Aims: This study was undertaken to compare the phytochemical compositions of several pilis oils produced by large jamu factories, local jamu producers, and home-based producers by GC-MS chemical analysis. Material and Methods: Pilis oils were sourced from multiple local manufacturers. All oils were extracted with hexane by Soxhlet extraction. The crude extracts were analyzed by GC-MS. Results: The oil composition of various pilis samples was complex and diversed. Many constituents were identified. The oil constituents of pilis could be classified into essential oils, fatty acids, and other nonpolar compounds. Pilis from the large factory had the lowest essential oil content, whilst the pilis from home-based producer was the highest essensial oil content. Twenty three main essential oils were detected. The amount of fatty acids in the pilis sourced from large factories was the highest. The fresh made pilis from home-based producers had a smaller amount of fatty acids than others. The other nonpolar constituents detected in all pilis were dimethoxyphenyl butadiene (DMPBD), shogaol and amyrin. Conclusion: Fresh made pilis from home-based producers had a higher amount of essential oils and also had higher variation, but only a small amount of fatty acids compared to the pilis from large jamu factories as well as local jamu producers.
Keywords: Essential oils; Jamu; Pilis; Topical Herbal Medicine; Indonesian traditional medicine; Ethnobotany